Influence of track foundation on the performance of ballast and concrete slab tracks under cyclic loading: Physical modelling and numerical model calibration. (29th March 2021) - Ramos, A.; Gomes Correia, A.; Calçada, R.; Alves Costa, P.; Esen, A.; Woodward, P.K.; Connolly, D.P.; Laghrouche, O.
Graphical abstract: Highlights: Development of a 3D model adapted to the ballast and slab tracks' physical models. Implementation of a permanent deformation model into the numerical model. Calibration of numerical models to improve reliability prediction. Calibration's results show good agreement between numerical and experimental data. Sensitivity analysis shows importance of effective cohesion in subgrade's long-term behaviour. Abstract: Ballast and slab railway track structures are constructed from different materials, thus requiring different maintenance strategies. Therefore, this paper compares the settlement performance of both structures using laboratory experiments, and calibrates numerical models based upon the results. Firstly, a comparison of the short and long-term behaviour of ballasted and slab tracks under cyclic loading is performed at full-scale. Both tracks have the same track foundation but a different track superstructure, and are subject to 3 million cycles of loading. The results are used to develop and calibrate the short-term response of a 3D finite element model of both track structures. They are also used to calibrate an empirical permanent deformation model for the track foundation, where the number of load cycles and stresses are the main inputs. A strong agreement is found between the numerical and experimental results. This justifies the track modelling approach in predicting the long-term behaviour of track structures where the subgrade is influential.